Nas “Quebradas do Inhanduí”, gênesis e exercício do bipartidarismo brasileiro: o regime civil-militar e as relações entre a Aliança Renovadora Nacional (ARENA) e o Movimento Democrático Brasileiro (MDB). (1966 – 1979) - Braga, Diego Garcia (Universidade do Vale do Rio dos Sinos, 2016)
This research about the Brazilian civil-military regime, is focused on the western border of Rio Grande do Sul state, to analyze the Brazilian two-party system (1966-1979), as well as intra- and inter-party relations involving the Arena and the MDB in Alegrete. It proposes to verify the way the typical structures of the dictatorship interacted with the characteristics of local politics and "vice versa". This way, the case study emphasizes the need to look at the authoritarian regime from the inland perspective, with held social dynamics completely different of the large urban centers. Thus, the two parties have been evaluated in structural, strategic and competitive levels, from municipal elections of 1968, 1972 and 1976, extending the approach to performance in the votings of Alegrete, relative for the General elections. Grounded on the contribution of History and Political Science, it discusses with the Brazilian case and the aspects regarding the operation of the two-party systems and in the fields of political parties as well as the intricate path that reflects on the areas of action of individuals and groups, in view of authoritarianism and increased unpredictability of the political field of the time. This allowed us to contradict many studies that indicate that the Brazilian bipartisanship was artificial and Arena and the MDB was the parties of "yes" and "yes, sir". In fact, nationally, both had their powers significantly restricted, especially the second. However, we consider this a dangerous generalization, because the search data of Alegrete city shows a different reality. The MDB won the elections for the executive and won majority in the local legislature during the period of greatest repression of the dictatorship. Arena, in turn, reversed this scenario in the second half of the 1970s, time when faced wear and tear in the national level, unlike the MDB. As a result, was founded that the two had some autonomy to chart their respective strategies, due to the local political characteristics, the intensification of fissions prior to 1966 and for the combination between other aspects created by the authoritarian regime. About this latter, the sublegendas are a important way to examine the parties disputes, although they have been created to benefit the Arena. Thus, we conclude that the Brazilian bipartisanship presented unique attributes, and is therefore quite complex. However, by linking national and local politics, the two-party system hardly can be considered artificial.
Keywords: Ditadura; Bipartidarismo; Alegrete; Dictatorship; Two-party system; ACCNPQ::Ciências Humanas::História